Cytometry by time-of-flight immunophenotyping identifies a blood Sjögren's signature correlating with disease activity and glandular inflammation - Mingueneau, Michael; Boudaoud, Saida; Haskett, Scott; Reynolds, Taylor L.; Nocturne, Gaetane; Norton, Elizabeth; Zhang, Xueli; Constant, Myrtha; Park, Daniel; Wang, Wenting; Lazure, Thierry; Le Pajolec, Christine; et al. (Journal of allergy and clinical immunology, 2016)
Mass cytometry has recently emerged as a promising tool for clinical research. However, few studies have demonstrated its benefit for patient stratification and biomarker identification. Primary Sjögren's syndrome (pSS) is a prototype of chronic autoimmune disease, the pathogenesis of which remains unclear and for which treatment does not exist. This observational case-control study was designed to discover new cellular biomarkers and therapeutic targets in patients with pSS. Forty-nine patients with pSS and 45 control subjects were enrolled for clinical evaluation and mass cytometry quantification of 34 protein markers in blood. For a third of these subjects, matched labial salivary gland biopsy specimens were also analyzed by mass cytometry and immunohistochemistry. In salivary gland biopsy specimens from patients with pSS, we identified a high number of activated CD8+ T cells, terminally differentiated plasma cells, and activated epithelial cells, pointing to new pathogenic mechanisms for future clinical intervention. In blood, we identified a 6-cell disease signature defined by decreased numbers of CD4 and memory B lymphocytes, decreased plasmacytoid dendritic cell numbers, and increased representation of activated CD4 and CD8 T cells and plasmablasts. These blood cellular components correlated with clinical parameters and, when taken together, clustered patients into subsets with distinct disease activity and glandular inflammation. This first application of mass cytometry to a well-stratified clinical cohort and small biopsy tissues establishes the benefits of such an approach for the discovery of new biomarkers and therapeutic targets. Similar high-dimensional immunophenotyping strategies could be implemented in longitudinal and interventional clinical settings in this and other disease areas. [Display omitted]